2021
DOI: 10.1007/s10461-021-03374-x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal PrEP Use in HIV-Uninfected Pregnant Women in South Africa: Role of Stigma in PrEP Initiation, Retention and Adherence

Abstract: Pregnant women in sub-Saharan Africa are at high risk of HIV acquisition and require effective methods to prevent HIV. In a cohort of pregnant women offered Pre-exposure prophylaxis (PrEP), we evaluate the relationship between internalized and anticipated stigma and PrEP initiation at first antenatal visit, 3-month continuation and adherence using multivariable logistic regression. High internalized and anticipated PrEP stigma are associated with lower PrEP care initiation at first antenatal visit (aOR interna… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…Of concern, a modelling study has predicted that 76,000 new cases of vertical transmission can be expected in South Africa between 2020 and 2030 if PrEP is not taken to scale with high levels of acceptance and persistence [ 12 ]. While some studies have identified barriers to PrEP adherence among pregnant and postpartum women such as stigma, overlapping side effects of PrEP use and pregnancy, and remembering to take PrEP [ 13 16 ], PrEP services for this population are limited [ 17 ], therefore data on PrEP use and adherence to PrEP among pregnant and postpartum women is sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Of concern, a modelling study has predicted that 76,000 new cases of vertical transmission can be expected in South Africa between 2020 and 2030 if PrEP is not taken to scale with high levels of acceptance and persistence [ 12 ]. While some studies have identified barriers to PrEP adherence among pregnant and postpartum women such as stigma, overlapping side effects of PrEP use and pregnancy, and remembering to take PrEP [ 13 16 ], PrEP services for this population are limited [ 17 ], therefore data on PrEP use and adherence to PrEP among pregnant and postpartum women is sparse.…”
Section: Introductionmentioning
confidence: 99%
“…An additional consideration is who a person discloses to, and the study among AGYW found that partners and parents provided the most support to participants who disclosed oral PrEP use [ 25 ]. Stigma was also found to be a barrier to oral PrEP continuation among pregnant women in South Africa [ 26 ]. We found that women who felt they would probably or definitely get infected with HIV had reduced odds of continuing oral PrEP at the final study visit.…”
Section: Discussionmentioning
confidence: 99%
“…This might be related to the timing of the questionnaire, as it was administered approximately 3 months after oral PrEP initiation, and women might have felt less at risk because of using daily oral PrEP. Alternatively, it is possible that women who felt at increased risk for HIV acquisition experienced additional challenges and barriers to oral PrEP continuation such as partner-related issues (i.e., difficulties with disclosure of oral PrEP use and issues relating to trust and/or fidelity in the relationship) or stigma (fear that others may think that oral PrEP is treatment for HIV) [ 26 ]. Surprisingly, women who had more than one sex partner had reduced odds of continuing oral PrEP, and this is an area that requires further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…More closely related to the present research is a small cluster of recent reports of PrEP use during pregnancy and postpartum for women in urban and rural settings in South Africa [42][43][44]. These investigations identified a number of the same concerns and influences on adherence that emerged from the present study, including the desire to remain free of HIV, fear of HIV-related stigma, the perception of being at high risk as a result of partner behavior, and disclosure of PrEP use and partner support.…”
Section: Discussionmentioning
confidence: 58%